TEMPOROMANDIBULAR JOINT DISORDERS DIAGNOSIS IN E DENTULOUS PATIENTS BASED ON DC-TMD AXIS I - Novita Gabriela Andreas; Rasmi Rikmasari; Taufik Sumarsongko (Fakultas Kedokteran Gigi Unjani, 2022)
Signs and symptoms of temporomandibular disorders/TMD often occur in edentulous patients. Etiology and clinical symptoms are different so the diagnosis is different. The diagnosis of TMD can be determined using Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) Axis I (clinical examination) and Axis 2 (psychological examination). The purpose of this study was to obtain a description of temporomandibular joint disorders in edentulous patients at the Dental Hospital of Padjadjaran University based on DC/TMD Axis I. This research was a descriptive study with a survey technique. The sample size was 32 patients that were collected by consecutive sampling. Temporomandibular disorders in edentulous patients were obtained by filling out symptom questionnaires and clinical examination based on DC/TMD Axis I, then grouped using the DC/TMD Axis I algorithm. The results showed that from 32 edentulous patients who visited the Dental Hospital of Padjadjaran University, there were 23 subjects diagnosed with temporomandibular disorders, with disc displacement with reduction (40.63%) as a major diagnosis, followed by local myalgia and myofascial pain in 2 subjects (6.25%) each, and arthralgia in 1 subject (3.12%). Subjects who had more than one diagnosis as many as 5 people (15.62%). According to the result of the study, most of the edentulous patients visiting the Dental Hospital of Padjadjaran University were diagnosed with temporomandibular disorders, and disc displacement with reduction was the most common diagnosis. DOI : 10.54052/jhds.v2n1.p97-110